Biosimilars in inflammatory bowel disease - Siegmund, B.; Atreya, Raja; Bokemeyer, B.; Kruis, W.; Mudter, J.; Sander, C.; Schreiber, S.; Reindl, W.; Zeissig, Sebastian; Kucharzik, T. (Zeitschrift für Gastroenterologie, 2016)
After the expiry date of the patent protection for Infliximab in 2013, the biosimilar CT-P13 was approved for indications in Crohn's disease and ulcerative colitis in adults as well as in children. The approval has been based on two randomized clinical studies indicating equivalence for the biosimilar with regard to pharmacokinetics, efficacy, as well as side-effects. The clinical experience since, in addition to multiple non-randomized studies, indicate a comparable efficacy and immunogenicity of the Infliximab biosimilar CT-P13 in inflammatory bowel disease. Thus, the introduction of the biosimilar as primary therapy seems to be justified. Tight monitoring of the safety of biosimilars with regard to efficacy and side effects has to be ensured.
EVALuna2:2203